The significance of U23 competitions in wrestling career - Latyshev, M.; Holovach, I.; Polianychko, O.; Tropin, Y.; Shtanagei, D.; Lakhtadyr, O. (Studia Sportiva, 2024)
Background. Designing the training of athletes should be based on specific goals and objectives at each stage of the long-term development. Each age stage in the development of an elite athlete has its own significance. The U23 competitions are organized to facilitate a smoother and more effective transition of wrestlers from junior to senior levels. The aim of the study is to determine the significance of performances in the U23 competitions for the subsequent development process of wrestlers. Materials and Methods. The following research methods have been used in the paper: the analysis of the scientific and methodological literature, the analysis of the official results, and methods of mathematical statistics. We have studied the sports careers of participants in the 2017, 2018, and 2019 World Championships in freestyle, Greco-Roman, and women's wrestling. A total of 1277 wrestlers` sporting biographies have been analyzed. Results. The majority of participants (73.7 %) in the U23 age category competitions previously competed at the junior level. Moreover, more than half of the athletes (58.4 %) had prior experience of participating in cadet competitions. It is worth noting that 63.7 % of all wrestlers participated in senior-level competitions, and 31.5 % of them achieved podium finishes. Among women, a higher percentage of athletes continue their careers (46.3 %) and achieve success (20.1 %) on the international stage after the U23 competitions. For male freestyle wrestlers, the figures are lower, with only 38.2 % continuing their careers. Conclusion. The analysis demonstrated that the U23 competitions, which serve as a continuation of the cadet and junior age groups, are part of the overall sequence of competitions in the development of wrestlers at the international level. However, the importance of the U23 competitions varies depending on the level of athletes, and they serve both as preparatory and main competitions within the athletes' training system.